Spatial Qualification Tests for Highly Selective Compact Micromachined Band Pass Planar Filters. (27th September 2012) - Hajj, Raghida; Chatras, Matthieu; Blondy, Pierre; Vendier, Olivier; Tschanum, Wolfgang; Courtade, Frederic
Abstract : A highly selective planar band pass filter is proposed for satellite receivers to suppress intermodulation components. The 4-pole filter has a center frequency of 19.825 GHz with a bandwidth of 240 MHz. The measured quality factor is over 600 and the insertion losses are 4.1 dB. The micromachining technological process is used to fabricate this filter. A BCB (benzocyclobutene) thin layer is used as an electrical and mechanical support for the filter. The compatibility of the BCB with the spatial constraints was tested. Various tests were accomplished for this purpose and the results of all these tests are presented in the paper. The tests showed a very small influence of the temperature variation and high temperature storage test and practically no influence of the radiation test on the circuit.